Значение муравья песчаного (Formica cinerea Мауr.) как энтомофага на Украине - Гримальский, В.И. (Вестник зоологии, 1969)
From some subspecies of Formica (Serviformica) cinerea Maуr, F. cinerea imitans Ruzsky is widely distributed in the Ukraine. It is often observed in the thin pine forests on the dry soils. It is established that in the forest stands with the presence of a great number of the above mentioned ants there are no seats of the needle-gnawing pests. F. cinerea imitans kills intensively the larvae of Neodiprion sertifer Geоffr. as well as caterpillars of Dendrolimus pini L. It is also aggressive to the ants of Formica rufa L. and F. polyctena Forst.